The Panca Pramana Learning Model on Students’ Cooperative Character and Scientific Literacy - Ni Komang Manik Sugiantari; I Gede Astawan; Gusti Ayu Putu Sukma Trisna (Indonesian Values and Character Education Journal, 2025)
Learning in elementary schools requires approaches that can enhance students’ abilities, particularly scientific literacy, which includes understanding, interpreting, and applying scientific concepts in everyday life. However, conventional teaching practices still commonly used in classrooms lead to low levels of cooperative character and scientific literacy among students. This study aims to examine the effect of the Panca Pramana learning model on students’ cooperative character and scientific literacy. The type of research conducted is a quasi-experiment with a Posttest Only Control Group Design. The population of this study consisted of all fifth-grade students, totaling 62 students, with the research sample being class VA and VB. Data collection methods and instruments included questionnaires and essay tests. The data analysis methods applied were descriptive statistical analysis and inferential analysis. The results showed that the average score of cooperative character in the experimental group (83.26) was higher than that of the control group (71.16), and the average score of scientific literacy in the experimental group (82.32) was higher than that of the control group (67.10). Based on the results of data analysis, cooperative character and scientific literacy were found to be significant (0.000 < 0.05). Thus, learning through the Panca Pramana learning model has a positive effect on the cooperative character and scientific literacy of fifth-grade students. The implication of this study is that by applying the Panca Pramana learning model, students better understand the learning material provided and participate more actively in the learning process.